Diagnosis Penyakit Ikan Mas Koki Menggunakan Metode Naive Bayes Classifier - Muhammad Hasbi Wa Kafa; Nurul Hidayat; Imam Cholissodin (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Indonesian state as a maritime country has thousands of species of fish. Various types of fish found in Indonesia, not only fish that can be consumed alone but Indonesia also has a variety of types of ornamental fish are very popular. One of the most popular ornamental fish is the goldfish chef, so it is not surprising that the demand for goldfish is increasing. From time to time many people are looking for a goldfish chef. Its high selling price also provides its own blessing for its business. Of course the goldfish cultivation is a gold field for farmers to gain profits. Cultivating the goldfish can be said is not difficult, but there is something to note in some ways because these fish including fish that are susceptible to disease. Illness may arise due to improper maintenance of the goldfish. The number of symptoms of the disease in the goldfish often makes cultivators difficult to identify the disease, so in the handling of goldfish disease chef also experienced a mistake. Therefore, a system that can help in identifying the goldfish disease properly. By using the method of calculation Naive Bayes Classifier has obtained 90% accuracy of the system which means the system can run well because the results from the system close to the similarity with the actual field facts.